Cognitive screening improves the predictive value of stroke severity scores for functional outcome 3–6 months after mild stroke and transient ischaemic attack: an observational study. Issue 9 (2nd September 2013) - Dong, YanHong; Slavin, Melissa Jane; Chan, Bernard Poon-Lap; Venketasubramanian, Narayanaswamy; Sharma, Vijay Kumar; Crawford, John D; Collinson, Simon Lowes; Sachdev, Perminder; Chen, Christopher Li-Hsian
Abstract : Objectives: To investigate the prognostic value of the neurocognitive status measured by screening instruments, the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE), individually and in combination with the stroke severity scale, the National Institute of Health Stroke Scale (NIHSS), obtained at the subacute stroke phase or the baseline (≤2 weeks), for functional outcome 3–6 months later. Design: Prospective observational study. Setting: Tertiary stroke neurology service. Participants: 400 patients with a recent ischaemic stroke or transient ischaemic attack (TIA) received NIHSS, MoCA and MMSE at baseline and were followed up 3–6 months later. Primary outcome measures: At 3–6 months following the index event, functional outcome was measured by the modified Rankin Scale (mRS) scores. Results: Most patients (79.8%) had a mild ischaemic stroke and less disability (median NIHSS=2, median mRS=2 and median premorbid mRS=0), while a minority of patients had TIA (20.3%). Baseline NIHSS, MMSE and MoCA scores individually predicted mRS scores at 3–6 months, with NIHSS being the strongest predictor (NIHSS: R 2 change=0.043, p<0.001). Moreover, baseline MMSE scores had a small but statistically significant incremental predictive value to the baseline NIHSS for mRS scores at 3–6 months, while baseline MoCA scores did not (MMSE: R 2 changes=0.006, p=0.03; MoCA: R 2 changes=0.004, p=0.083). However, in patients with more severe stroke at baseline (defined as NIHSS>2), baseline MoCA and MMSE had a significant and moderately large incremental predictive value to the baseline NIHSS for mRS scores at 3–6 months (MMSE: R 2 changes=0.021, p=0.010; MoCA: R 2 changes=0.017, p=0.021). Conclusions: Cognitive screening at the subacute stroke phase can predict functional outcome independently and improve the predictive value of stroke severity scores for functional outcome 3–6 months later, particularly in patients with more severe stroke.